Combined action observation and motor imagery : is a functional equivalence approach more effective? - Tan, Cher Han (2017)
The aim of this study was to compare the effects between PETTLEP-based (Physical, Environment, Task, Timing, Learning, Emotion, Perspective; Holmes and Collins, 2001) motor imagery (MI) combined with 1st person point-of-view (PPOV) action observation (AO) and PETTLEP-based MI combined with 3rd PPOV AO on the improvement of a novel motor skill – golf putting. Pre- and post-tests consist of a 15-ball putting task. Twenty one participants, with no experience in golf and MI, were assigned to one of three groups based on their imagery ability, and underwent three intervention sessions inclusive of physical practice. A “Functional Equivalence” group was required to watch an internal perspective video of a golfer putting, while a “Traditional” group was required to watch an external perspective video of a golfer putting. Both groups received PETTLEP-based MI after watching the video. Control participants were required to spend a similar amount of time watching an interview of a famous golfer, and controlled for physical practice effects. An analysis of variance (ANOVA) was significant, p < .001, η² = .55. There were also significant interaction effects between types of intervention and time, p < .05, η² = .31; post-hoc tests were insignificant (p > .05). The significant interaction effect suggests that both interventions were effective in improving motor skill performance. Although the three groups did not differ in their overall performance, the Functional Equivalence group was the only group that showed significant improvement from pre-test to post-test (p < .05). This suggests that having a congruent perspective in AO and MI may be more effective in improving motor skill performance.